Effect of end-of-production light treatment under different light/dark alternating frequencies on ascorbic acid accumulation and metabolism of hydroponic lettuce - Yu, Dong; Li, Zonggeng; Hu, Jiangtao; Wang, Fang; Lu, Wei; Yuan, Quan; Wang, Sen; Zhou, Chengbo; Yang, Qichang (Frontiers in Plant Science, 2025)
IntroductionThis study investigated the effects of different light/dark alternation cycles on ascorbic acid (AsA) metabolism and oxidative stress in hydroponic lettuce under end-of-production (EOP) conditions characterized by high light intensity and a high blue-light ratio (500 mmol·m⁻²·s⁻¹, red:blue = 1:1).MethodsFour treatments were applied: RB1 (continuous illumination), RB2 (4 h light/4 h dark/4 h light), RB4 (three cycles of 2 h light/2 h dark plus a final 2 h light), and RB8 (seven cycles of 1 h light/1 h dark with a final 1 h light).ResultsThe results revealed that AsA content exhibited an initial increase followed by a decrease with increasing alternation frequency, peaking under the RB2 treatment. Specifically, RB2 achieved the highest AsA accumulation, which was 11.8%, 28.5%, and 41.6% greater than in RB1, RB4, and RB8, respectively. This enhancement was attributed to the synchronous upregulation of the gene expression and enzymatic activity of GLDH, as well as key enzymes in the ascorbate-glutathione cycle (APX, MDHAR, and DHAR). Oxidative stress indicators (H₂O₂, MDA) decreased with increased light/dark alternation frequency.DiscussionTherefore, the RB2 treatment, by coordinating reactive oxygen species (ROS) induction and promoting the simultaneous upregulation of expression and activity in the AsA metabolic enzyme system, serves as an energy-efficient strategy for improving the nutritional quality of lettuce in controlled environments.